Economic design of a Vp X̄ chart - De Magalhães, Maysa S.; Epprecht, Eugenio K.; Costa, Antonio F.B. [UNESP] (Elsevier, 2001)
We develop an economic model for X̄ control charts having all design parameters varying in an adaptive way, that is, in real time considering current sample information. In the proposed model, each of the design parameters can assume two values as a function of the most recent process information. The cost function is derived and it provides a device for optimal selection of the design parameters. Through a numerical example one can foresee the savings that the developed model possibly provides. © 2001 Elsevier Science B.V. All rights reserved.
Keywords: Control charts; Expected cost; Process control; Variable design parameters; Costs; Economics; Mathematical models; Quality control; Statistical process control